The global factors driving common inflation in ASEAN - Pham Thi Tuyet Trinh; Le P. A. Nhan (Global Business & Finance Review (GBFR), 2023)
Purpose: This study investigates the comovements of inflation across ASEAN countries and identifies the global factors driving the common inflation dynamics of the region. Design/methodology/approach: The study uses a two-step approach. The dynamic latent factor model is first employed to estimate the common inflation of the region in the period between 2000Q1 and 2022Q2. In the second step, a bound test approach to autoregressive distributed lag (ARDL) methodology is employed to estimate the model of common inflation, which is constructed based on the aggregate supply - aggregate demand (AS-AD) framework. Findings: The study finds a common factor of inflation across ASEAN countries. The analysis of variance decomposition indicates the significant role of common inflation in the variations of individual countries' inflation. World economic growth, oil price change, non-fuel commodity price change, and trade openness are the main drivers of ASEAN common inflation in both short and long terms. Research limitations/implications: The study focuses mainly on supply-side factors, although some demand-side factors are involved. Future studies should pay more concerns on the trade linkages among regional countries and the similarities in goals in the region. Originality/value: The study examines the common inflation component across ASEAN countries, which has not been sufficiently investigated. It also evaluates the drivers at the global level of common inflation, which has limited empirical evidence.
Keywords: 650; Inflation comovements; Dynamic factor model; Global factors; ARDL; ASEAN